Clinical Characteristics and Growth Hormone Treatment in Patients with Prader-Willi Syndrome - Aydilek Dağdeviren Çakır (JCRPE, 2021)

(untitled)
Objective:To investigate clinical characteristics and response to growth hormone (GH) treatment in patients with Prader-Willi syndrome (PWS) in Turkey.Methods:The data of 52 PWS patients from ten centers was retrospectively analyzed. A nation-wide, web-based data system was used for data collection. Demographic, clinical, genetic, and laboratory data and follow-up information of the patients were evaluated.Results:The median age of patients at presentation was 1.5 years, and 50% were females. Genetic analysis showed microdeletion in 69.2%, uniparental disomy in 11.5%, imprinting defect in 1.9% and methylation abnormality in 17.3%. Hypotonia (55.7%), feeding difficulties (36.5%) and obesity (30.7%) were the most common complaints. Cryptorchidism and micropenis were present in 69.2% and 15.3% of males, respectively. At presentation, 25% had short stature, 44.2% were obese, 9.6% were overweight and 17.3% were underweight. Median age of obese patients was significantly higher than underweight patients. Central hypothyroidism and adrenal insufficiency were present in 30.7% and 4.7%, respectively. Hypogonadism was present in 75% at normal age of puberty. GH treatment was started in 40% at a mean age of 4.7±2.7 years. After two years of GH treatment, a significant increase in height SDS was observed. However, body mass index (BMI) standard deviation (SDS) remained unchanged.Conclusion:The most frequent complaints were hypotonia and feeding difficulty at first presentation. Obesity was the initial finding in 44.2%. GH treatment was started in less than half of the patients. While GH treatment significantly increased height SDS, BMI SDS remained unchanged, possibly due to the relatively older age at GH start.